TOR signaling regulates liquid phase separation of the SMN complex governing snRNP biogenesis - Schilling, Maximilian Thomas; Prusty, Archana B.; Boysen, Björn; Oppermann, Felix Sebastian; Riedel, Yannick L.; Husedzinovic, Alma; Rasouli, Homa; König, Angelika; Ramanathan, Pradhipa; Reymann, Jürgen; Erfle, Holger; Daub, Henrik; et al. (Cell reports, 2021)
The activity of the SMN complex in promoting the assembly of pre-mRNA processing UsnRNPs correlates with condensation of the complex in nuclear Cajal bodies. While mechanistic details of its activity have been elucidated, the molecular basis for condensation remains unclear. High SMN complex phosphorylation suggests extensive regulation. Here, we report on systematic siRNA-based screening for modulators of the capacity of SMN to condense in Cajal bodies and identify mTOR and ribosomal protein S6 kinase β-1 as key regulators. Proteomic analysis reveals TOR-dependent phosphorylations in SMN complex subunits. Using stably expressed or optogenetically controlled phospho mutants, we demonstrate that serine 49 and 63 phosphorylation of human SMN controls the capacity of the complex to condense in Cajal bodies via liquid-liquid phase separation. Our findings link SMN complex condensation and UsnRNP biogenesis to cellular energy levels and suggest modulation of TOR signaling as a rational concept for therapy of the SMN-linked neuromuscular disorder spinal muscular atrophy.